BOHR’S THEOREM FOR DOUBLE TRIGONOMETRIC INTERPOLATION POLYNOMIALS - Nurbekyan, A.R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
H. Bohr’s Theorem on uniform convergence of double trigonometric interpolation polynomials is proved.
Keywords: trigonometric interpolation, superposition, homeomorphism, convergence